Foliar P-Fractions Allocation of Karelinia caspia and Tamarix ramosissima Are Driven by Soil and Groundwater Properties in a Hyper-Arid Desert Ecosystem - Gao, Yanju; Zhang, Zhihao; Zhang, Bo; Yin, Hui; Chai, Xutian; Xu, Mengqi; Tariq, Akash; Zeng, Fanjiang (Frontiers in Plant Science, 2022)
Allocation patterns of foliar phosphorus (P) fractions across various vegetation types generally reflect adaptability to P-impoverished environments. However, the allocation of foliar-P fractions within the desert herb Karelinia caspia (K. caspica) and shrub Tamarix ramosissima (T. ramosissima) in soils with different environment-P availability, and the impact of soil and groundwater properties on foliar-P fractions allocation, remains unclear. Foliar-P fractions (metabolites-P, nucleic acid-P, structural-P, and residual-P) of K. caspica and T. ramosissima, as well as the properties of 0–60 cm deep soil under their canopy and groundwater were determined at four different environment-P sites. Results found that as environment-P availability decreased, both plants allocated higher proportions of foliar-P to nucleic acid-P than to metabolites-P and structural-P. With the exception of residual-P, foliar-P fractions were markedly higher for K. caspica than T. ramosissima. Soil Olsen-P, NO3–-N, soil water content, electrical conductivity (EC), groundwater EC, and total dissolved solids played an important role in allocating foliar P-fractions for both K. caspica and T. ramosissima. Compared to K. caspica, the foliar-P fractions of T. ramosissima were more tightly bounded to groundwater than soil properties. Overall, these findings show how desert plants flexible take advantage of foliar-P in low environment-P availability and illustrate foliar-P fractions allocation of desert plants is driven by soil and groundwater properties.